Confocal Raman microspectroscopy on excised human skin: uncertainties in depth profiling and mathematical correction applied to dermatological drug permeation - Tfayli, A.; Piot, O.; Manfait, M. (Journal of biophotonics, 2008)
Confocal Raman microspectroscopy represents the advantage of giving structural and conformational information on samples without any destructive treatment. Recently, several studies were achieved to study the skin hydration, endogenous and exogenous molecules repartition in the skin using the confocal feature of this technique. Meanwhile, when working through a material boundary with a different refractive index, the main limitation remains the spatial precision, especially the distortion in the depth and the depth resolution. Recently, several authors described mathematical models to correct the depth and the resolution values. In this study, we combined theoretical approaches, proposed by different authors with experimental measurements to try to find out the most appropriate approach for correction. We then applied the corrections on in‐depth profiles tracking the penetration of Metronidazole, a drug produced by Galderma for rosacea treatment, through excised human skin. (© 2008 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)